Spondyloarthritis Patients Suffer Increased Risk of Renal Complications Compared With General Population: A Retrospective Observational Study - Xiao, Min; Lv, Qing; Zhang, Yanli; Tu, Liudan; Yang, Mingcan; Lin, Zhiming; Liao, Zetao; Jiang, Yutong; Zheng, Xuqi; Li, Xiaomin; Wei, Qiujing; Cao, Shuangyan; et al. (Frontiers in Pharmacology, 2019)
The objective of this study was to identify the prevalence and risk factors of renal complications of spondyloarthritis (SpA) patients, and to assess increased risks compared to general people. We conducted a retrospective study enrolled consecutive SpA patients from inpatient department and age, sex-matched general population (GP). The renal disorders investigated in this study contained decreased estimated glomerular filtration rate (eGFR), hematuria, proteinuria and nephrolithiasis. A total of 350 admitted SpA patients with complete medical records and 323 age and sex-matched GP were enrolled. Most SpA patients was male (n=283, 80.9%) and the mean age was 31.61±10.73 years old. Among 350 SpA patients, 29 (8.8%) suffered from hematuria, 6 (1.8%) suffered from proteinuria, 1 (0.3%) had decreased eGFR, and 27 (13.0%) presented with nephrolithiasis. The relative risk (RR) of nephrolithiasis in SpA compared to GP was 2.24 (95% CI, 1.00-4.98), and the RR of renal insufficiency was 2.04 (95% CI, 1.11-3.77). In univariate analysis, nephrolithiasis was significantly associated with age, age of onset, smoking, extra-articular manifestation and bamboo spine. Renal insufficiency was significantly associated with age, peripheral manifestation, serum albumin, C-reactive protein and erythrocyte sedimentation rate. In multivariable analysis, only extra-articular manifestation (OR=8.43, 95% CI, 1.65-43.06, p=0.010) and bamboo spine (OR=3.47, 95% CI, 1.01-12.06, p=0.049) remained significantly associated with nephrolithiasis. However, no variable was recognized as independent risk factors for renal insufficiency. Renal complications are more common in SpA patients, with more than two-fold increased risk compared with GP. Extra-articular manifestation and bamboo spine are the independent risk factors of renal diseases in SpA patients.